Origins of strabismus and loss of binocular vision - Bui Quoc, Emmanuel; Milleret, Chantal (Frontiers in Integrative Neuroscience, 2014)
Strabismus is a frequent ocular disorder that develops early in life in humans. As a general rule, it is characterized by a misalignment of the visual axes which most often appears during the critical period of visual development. However other characteristics of strabismus may vary greatly among subjects, for example, being convergent or divergent, horizontal or vertical, with variable angles of deviation. Binocular vision may also vary greatly. Our main goal here is to develop the idea that such “polymorphy” reflects a wide variety in the possible origins of strabismus. We propose that strabismus must be considered as possibly resulting from abnormal genetic and/or acquired factors, anatomical and/or functional abnormalities, in the sensory and/or the motor systems, both peripherally and/or in the brain itself. We shall particularly develop the possible “central” origins of strabismus. Indeed, we are convinced that it is time now to open this “black box” in order to move forward. All of this will be developed on the basis of both presently available data in literature (including most recent data) and our own experience. Both data in medicine and biology will be referred to. Our conclusions will hopefully help ophthalmologists to better understand strabismus and to develop new therapeutic strategies in the future. Presently, physicians eliminate or limit the negative effects of such pathology both on the development of the visual system and visual perception through the use of optical correction and, in some cases, extraocular muscle surgery. To better circumscribe the problem of the origins of strabismus, including at a cerebral level, may improve its management, in particular with respect to binocular vision, through innovating tools by treating the pathology at the source.